Penerapan Etika Bisnis Islam Terhadap Kelangsungan Pembiayaan SPBU Mini Di KSPPS Bina Syariah Ummah Jawa Timur - Agus Wahyu Irawan (Universitas Islam Lamongan, 2020)
Islamic financial institutions are developed as an alternative to the practice of people who want sharia transactions. Criticism of conventional financial institutions by the concept of sharia is not rejecting cooperatives. However, providing solutions to the transaction community that is avoided from the elements of usury, gambling (maysi>r), uncertainty (ghara>r), and inner. With the prohibition of usury, maysi>r, ghara>r, and heart in the transactions of financial institutions, they can instead apply contracts in accordance with Islamic business ethics. The purpose of this article is to find out the application of Islamic business ethics to the financing of mini gas stations at KSPPS Bina Syariah Ummah, East Java. The method used in writing this article is a descriptive qualitative. Analysis method is based on field studies. Analytical studies are intensive testing, using various sources of qualitative evidence. From the data obtained is then arranged according to the rules and analysis in accordance with the rules of writing so as to facilitate the discussion of existing problems. Methods of data collecting: interview, observation and documentation data. With this method, the author wants to examine how Islamic business ethics views about financing mini gas stations. The results of this study shows that application of business ethics in business is appropriate and good, the impact on the business is also good. So Islamic business ethics has been tested and brought benefits if applied properly. Keywords: islamic ethics implementation, SPBU funding continuity